Observation of non-metallic inclusions on repeatedly quenched SAE 52100 bearing steel fracture surfaces. (1st January 2012) - Mizobe, Koshiro; Santos, Edson Costa; Honda, Takashi; Koike, Hitonobu; Kida, Katsuyuki; Shibukawa, Takuya
Martensitic high carbon high strength SAE 52100 bearing steel is one of the main alloys used for rolling contact applications where high wear resistance are required. Due to its high fatigue strength, SAE 52100 is recently being used not only for the production of bearings but also shafts. Refining of prior austenite grain through repeated quenching is a procedure that can be used to enhance the material's strength. In this work, the microstructure of repeatedly quenched SAE 52100 steel and its fatigue strength under rotating bending were investigated. It was found that repeated furnace heating and quenching effectively refined the martensitic structure and increased the retained austenite content. Repeated quenching was found to improve the fatigue strength of SAE 52100.